2016
DOI: 10.1016/j.heliyon.2016.e00202
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and rapid instrumental methods as a combined tool for quality control of cooked ham

Abstract: In this preliminary investigation, different commercial categories of Italian cooked pork hams have been characterized using an integrated approach based on both sensory and fast instrumental measurements. For these purposes, Italian products belonging to different categories (cooked ham, “selected” cooked ham and “high quality” cooked ham) were evaluated by sensory descriptive analysis and by the application of rapid tools such as image analysis by an “electronic eye” and texture analyzer. The panel of traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…In the present study, cooking with different temperatures showed that odor and taste were more significant in describing drycured ham than color, texture, and juiciness. These results were not in line with previous studies presented in literature which found that the largest difference between cooked samples with respect to color and texture was caused by the cooking temperature (Barbieri et al, 2016). The difference could be explained by the fact that Jinhua ham owned an outstanding flavor parameter (Huan et al, 2005).…”
Section: Sensory Characteristics Of Cooked Hamcontrasting
confidence: 96%
“…In the present study, cooking with different temperatures showed that odor and taste were more significant in describing drycured ham than color, texture, and juiciness. These results were not in line with previous studies presented in literature which found that the largest difference between cooked samples with respect to color and texture was caused by the cooking temperature (Barbieri et al, 2016). The difference could be explained by the fact that Jinhua ham owned an outstanding flavor parameter (Huan et al, 2005).…”
Section: Sensory Characteristics Of Cooked Hamcontrasting
confidence: 96%
“…These findings point out the accuracy of both NIRS and data mining techniques for prediction of sensory attributes of cooked loins. This is in agreement with previous studies applying NIRS to cooked ham and lamb meat and using partial least square and partial least square regression. Besides that, some have proposed the use of NIRS to predict physicochemical parameters in pork meat products …”
Section: Resultssupporting
confidence: 93%
“…In addition, Alamprese and Casiraghi allowed the authentication of fish fillets by means of NIRS. There also are some studies focused on analysing quality characteristics of cooked meat by using NIRS …”
Section: Introductionmentioning
confidence: 99%
“…Principal component analysis (PCA) is an orthogonal projection of the data onto a lower-dimensional space such that the variance of the projected data is maximized [52,53]. This method has been widely used in sensory analysis [54,55,56,57,58,59,60,61]. Furthermore, it is a core component of the internal and external preference mappings.…”
Section: Methodsmentioning
confidence: 99%